ANALYSIS OF THE IMPEACHMENT OF THE VICE PRESIDENT IN THE PERSPECTIVE OF INDONESIAN LAW AND FIQH SIYASAH: A CASE STUDY OF GIBRAN RAKABUMING RAKA: ANALISIS PEMAKZULAN WAKIL PRESIDEN DALAM PERSPEKTIF HUKUM INDONESIA DAN FIQH SIYASAH: STUDI KASUS GIBRAN RAKABUMING RAKA - Muhammad Abduh; Dhiauddin Tanjung; Ramadhan Syahmedi Siregar (SOSIOEDUKASI, 2025)
This article intends to analyze the impeachment of the vice president from the point of view of Indonesian law and Siyasah Islamiyah, with special emphasis on the case of Indonesian Vice President Gibran Rakabuming Raka. The impeachment of high-ranking state officials, such as the vice president, is an important issue [there is an Indonesian system of government that adheres to the presidential system. The discussion on the impeachment of Gibran Rakabuming Raka as Vice President of the Republic of Indonesia has caused a deep debate, not only from the point of view of constitutional law but also from the perspective of leadership ethics and political legitimacy. This research is a juridical-normative research. The data sources of this study are composed of primary and secondary data sources collected through literature studies. After accumulation, the data is analyzed by qualitative descriptive analysis method. The findings of this study indicate that the process of impeachment of Vice Presidents in Indonesia is strictly regulated and very limited. The 1945 Constitution contains clear requirements, namely that there must be serious violations of the law and involve three institutions. This makes impeachment difficult to carry out without strong evidence. In the context of Siyasah Islamiyah, a leader can be impeached if he loses trust and justice, which emphasizes the importance of moral responsibility. Gibran's case shows a clash between legality and legitimacy, where even if he is officially elected, the process undermines the trust of the public.